Arif Pengaruh Latihan Pliometrik Single Leg Bound terhadap Kecepatan Tendangan Lurus Depan Pencak Silat di Kabupaten Pemalang - Husain, Arif Nur; Raharjo, Agus (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the effect of Single Leg Bound on the speed of the pencak silat front kick in Pemalang Regency. The method used was quantitative. The samples used were all pencak silat athletes in Pemalang Regency (total sampling) totaling 24 athletes. The instrument for the test used in this study used the instructions for the front kick speed skill test from Johansyah Lubis. The data analysis technique uses calculations through the help of SPSS using the paired sample test method with the provisions of the Sig value. (2-tailed) < 0.05 then H0 is rejected and Ha is accepted (there is an effect). And using t-test statistics (t-test) with a sign of 5% and d.b = n-1. Research Results To test this hypothesis, a significance level of 5% or 0.05 was used. The provisions of this hypothesis testing are that H0 is rejected and Ha is accepted if T-count > T-table, on the other hand H0 is accepted and Ha is rejected if T-count < T-table. Based on the results of the calculation analysis in this study, there was a change in the speed of the pencak silat front straight kick after performing single leg bound plyometric exercises on pencak silat athletes in Pemalang Regency, as evidenced by the results of calculations using the help of spss.21 showing the value of Sig. (2 tailed) that is .000 < 0.05 then H0 is rejected and Ha is accepted (there is/is an effect).